Financing of exports : a guide for developing countries and transition economies - Surcliffe, Leni G. ed. (ITC GenevaCH, 1997)
Reviews financial measures to promote exports. Deals with the role of commercial banks and export credit agencies; private-sector credit insurance; and, finance targeted to the informal sector (micro-credits). Explains the Grameen Banking Approach and describes experiments in providing micro-credits for exporters in selected developing countries.